EFFECT OF PLANT GROWTH REGULATORS AND MICRONUTRIENTS ON YIELD ATTRIBUTES OF GUAVA (PSIDIUM GUAJAVA L.) CV. L-49 - Avdhesh Kumar,; Bhagwan Deen, (The Bioscan, 2026)
The present investigation entitled “Studies on effect of foliar feeding of micronutrients and plant growth regulators on fruiting behaviour, yield, quality and storability of Guava (Psidium guajava L.) fruits cv. L-49” was carried out during the year 2023-24 and 2024-2025 at Main Experiment Station, Department of Horticulture, ANDUAT, Kumarganj, Ayodhya, Uttar Pradesh, India. The treatments comprised of the spraying of different PGRs and micronutrients to study the yield attributes of guava fruits cultivar L-49. The experiment was conducted in randomized block design (RBD) with eleven treatments and three replications. The experiment consisted of eleven treatments including T1 (Control), T2 (ZnSO4 0.5%), T3 (Borax 0.5 %), T4 (NAA 40 ppm), T5 (GA3 40 ppm), T6 (ZnSO4 @ 0.5 % + Borax @ 0.5%), T7 (ZnSO4 0.5% + NAA 40 ppm) T8 (ZnSO4 0.5% + GA3 40 ppm), T9 (Borax 0.5% + NAA 40 ppm) T10 (Borax 0.5% + GA3 40 ppm) T11 (GA3 40 ppm + NAA 40 ppm) Were used for this study. The maximum fruit weight (217.05 g), maximum fruit length (9.35 cm), maximum fruit Width (6.15 cm), maximum fruit volume (196.16 cc), maximum fruit specific gravity (1.19) and highest fruit yield per plant (45.64 kg) were observed with the foliar application of T11 (GA₃ 40 ppm + NAA 40 ppm) under the agroclimatic condition of Eastern Uttar Pradesh of India. Keywords Guava, ZnSO4, NAA, Yield, Specific, Gravity